Case Report: Clostridial Gas Gangrene of Pelvic Wall After Laparoscopic Rectal Cancer Surgery Induced Fatal Sepsis - Wang, Xing; Jiao, Simin; Sun, Zhen; Wang, Zhicheng; Wang, Xudong; Liu, Tianzhou (Frontiers in Surgery, 2022)
Clostridial gas gangrene is an unusual but fast-spreading necrotic infection of soft tissue relevant to high mortality rates. We report a case of postoperative gas gangrene of pelvic wall, the scrotum and perineal site with very acute onset and rapid progression of symptoms after a laparoscopic radical resection for rectal cancer. Although potentially treatable with appropriate antibiotic cover and urgent thorough surgical debridement, this case still developed irreversibly into fulminant and fatal sepsis. The possible etiologic factors, better measures of diagnosis and treatment are discussed and the relevant literature is reviewed.